Frequency of coinfection by respiratory pathogens and its impact on the prognosis of patients with COVID-19.: Frecuencia de coinfección por patógenos respiratorios y su impacto en el pronóstico de pacientes con COVID-19. - Quiñones-Laveriano, Dante Manuel (2021)
Introduction: Co-infection between other microorganisms and SARS-CoV-2, such as viruses, bacteria and fungi, is an important factor in the management of COVID-19, which could increase the difficulties in diagnosis, management, prognosis, and even increase the mortality. Objectives: The objective of this review is to describe the published scientific evidence regarding coinfection in patients with COVID-19. Methods: A bibliographic search of studies published in Spanish or English was carried out using the PubMed, The Cochrane Library and Google Scholar search engines. Studies published between January 2020 and January 24, 2021 were assessed. Results: 25 articles from various continents (America, Asia and Europe) were included. All the studies had patients with a confirmed diagnosis of COVID-19 added to some other test that identified some co-infection. We identified 18 studies that showed bacterial coinfection, 17 studies of viral coinfection and 5 studies of fungal coinfection. The prevalence of coinfection showed extremely dissimilar figures according to the population studied and diagnostic criteria. Conclusions: The presence of coinfection seems to be linked to a higher frequency of unfavorable outcomes. However, it is important to develop Latin American studies, given the heterogeneity in the studies seen in different countries. Standardized definitions should be developed in order to be able to assess the impact of co-infections in patients with a diagnosis of COVID-19